Bioaccessibility and Gut Metabolism of Free and Melanoidin-Bound Phenolic Compounds From Coffee and Bread - Alves, Genilton; Lobo, Leandro Araújo; Domingues, Regina Maria Cavalcanti Pilotto; Monteiro, Mariana; Perrone, Daniel (Frontiers in Nutrition, 2021)
The aim of this study was to investigate the bioaccessibility and gut metabolism of free and melanoidin-bound phenolic compounds from coffee and bread. Phenolics from coffee were predominantly found in free forms (68%, mainly chlorogenic acids), whereas those from bread were mostly bound to melanoidins (61%, mainly ferulic acid). Bioacessibility of coffee total free phenolics slightly decreased during simulated digestion (87%, 86% and 82% after the oral, gastric, and intestinal steps, respectively), with caffeoylquinic acids being isomerized and chlorogenic acids being partially hydrolyzed to the corresponding hydroxycinnamic acids. Bioacessibility of bread total free phenolics decreased during simulated digestion (91%, 85% and 67% after the oral, gastric, and intestinal steps, respectively), probably related to complexation with the proteins in simulated gastric and intestinal fluids. Upon gut fermentation, the bioaccessibility of total free phenolics from both coffee and bread decreased, mainly after the first 4 h (56% and 50%, respectively). Caffeic and ferulic acids were the predominant metabolites found during coffee and bread gut fermentation, respectively. Melanoidin-bound phenolics from coffee and bread were progressively released after the gastric and intestinal steps, probably due to hydrolysis caused by the acidic conditions of the stomach and the action of pancreatin from the intestinal fluid. The bioaccessibilities of all phenolics from coffee and bread melanoidins after the gastric and intestinal steps were, on average, 11% and 26%, respectively. During gut fermentation, phenolics bound to both coffee and bread melanoidins were further released by the gut microbiota, whereas those from coffee were also metabolized. This difference could be related to the action of proteases on melanoproteins during gastrointestinal digestion, probably anticipating phenolics release. Nevertheless, bioaccessibilities of melanoidin-bound phenolics reached maximum values after gut fermentation for 24 h, of 50% for coffee and 51% for bread. In conclusion, the bioaccessibilities of coffee and bread free phenolics during simulated digestion and gut fermentation were remarkably similar, and so were the bioaccessibilities of coffee and bread melanoidin-bound phenolics.